Molecular findings and clinical data in a cohort of 150 patients with anophthalmia/microphthalmia. (7th October 2013) - Chassaing, N.; Causse, A.; Vigouroux, A.; Delahaye, A.; Alessandri, J.‐L.; Boespflug‐Tanguy, O.; Boute‐Benejean, O.; Dollfus, H.; Duban‐Bedu, B.; Gilbert‐Dussardier, B.; Giuliano, F.; Gonzales, M.; et al.
<x xml:space="preserve">Abstract</x> Anophthalmia and microphthalmia (AM) are the most severe malformations of the eye, corresponding respectively to reduced size or absent ocular globe. Wide genetic heterogeneity has been reported and different genes have been demonstrated to be causative of syndromic and non‐syndromic forms of AM. We screened seven AM genes [GDF6 (growth differentiation factor 6), FOXE3 (forkhead box E3), OTX2 (orthodenticle protein homolog 2), PAX6 (paired box 6), RAX (retina and anterior neural fold homeobox), SOX2 (SRY sex determining region Y‐box 2), and VSX2 (visual system homeobox 2 gene)] in a cohort of 150 patients with isolated or syndromic AM. The causative genetic defect was identified in 21% of the patients (32/150). Point mutations were identified by direct sequencing of these genes in 25 patients (13 in SOX2, 4 in RAX, 3 in OTX2, 2 in FOXE3, 1 in VSX2, 1 in PAX6, and 1 in GDF6). In addition eight gene deletions (five SOX2, two OTX2 and one RAX) were identified using a semi‐quantitative multiplex polymerase chain reaction (PCR) [quantitative multiplex PCR amplification of short fluorescent fragments (QMPSF)]. The causative genetic defect was identified in 21% of the patients. This result contributes to our knowledge of the molecular basis of AM, and will facilitate accurate genetic counselling.